A World in Transition: Rethinking the Current Global Order - Mohammad Javad Zarif; Sasan Karimi (China Quarterly of International Strategic Studies)
Over the past three decades, the world has experienced significant turbulence, shaped by conflicts, global transformations, and crises within the international community. The end of the Cold War disrupted a long-established order, leaving both policymakers and scholars in uncharted territory. During the Cold War, international relations were more predictable, offering a stable framework for strategic analysis. In the aftermath, a wave of activity in the United States — fueled by a sense of victory — sought to redefine the future. This effort went beyond physical actions, extending into research institutions, think tanks, and academia, all striving to chart new courses in both practice and theory. Yet, the rapid pace of change and the fluid nature of the global landscape led to numerous missteps and misjudgments, affecting both major and middle powers to varying degrees. This paper examines the consequences of these intellectual efforts and the transitional phase that followed. It explores the defining features of this period and the forces that have shaped it. By shedding light on these dynamics, the paper aims to equip policymakers and scholars with the insights needed to better understand and influence the emerging international order. The ultimate goal is to foster a practical understanding of the challenges and opportunities ahead, helping navigate the complexities of the evolving global landscape.